17β-Estradiol Treatment Attenuates Neurogenesis Damage and Improves Behavior Performance After Ketamine Exposure in Neonatal Rats - Li, Weisong; Li, Huixian; Wei, Haidong; Lu, Yang; Lei, Shan; Zheng, Juan; Lu, Haixia; Chen, Xinlin; Liu, Yong; Zhang, Pengbo (Frontiers in Cellular Neuroscience, 2019)
Ketamine exposure disturbed normal neurogenesis in the developing brain and resulted in subsequent neurocognitive deficits. 17β-estradiol provides robust neuroprotection in a variety of brain injury models in animals of both sexes and attenuates neurodegeneration induced by anesthesia agents. In the present study, we aimed to investigate whether 17β-estradiol could attenuate neonatal ketamine exposure-disturbed neurogenesis and behavioral performance. We treated 7-day-old (Postnatal day 7, PND 7) Sprague-Dawley rats and neural stem cells (NSCs) with either normal saline, ketamine, or 17β-estradiol before/after ketamine exposure, respectively. At PND 14, the rats were decapitated to detect neurogenesis in the subventricular zone (SVZ) and subgranular zone (SGZ) of the hippocampus by immunofluorescence staining. The proliferation, neuronal differentiation, and apoptosis of NSCs were assessed by immunohistochemistry method and TUNEL assay, respectively. The protein levels of cleaved caspase-3 in vivo in addition to GSK-3β and p-GSK-3β in vitro were examined by western blotting. Spatial learning and memory abilities were assessed by Morris water maze (MWM) test at PND 42–47. Ketamine exposure decreased cell proliferation in the SVZ and SGZ, inhibited NSC proliferation and neuronal differentiation, promoted NSC apoptosis and led to adult cognitive deficits. Furthermore, ketamine increased cleaved caspase-3 in vivo and decreased the expression of p-GSK-3β in vitro. Treatment with 17β-estradiol could attenuate ketamine-induced changes both in vivo and in vitro. For the first time we showed that 17β-estradiol alleviated ketamine-induced neurogenesis inhibition and cognitive dysfunction in the developing rat brain. Moreover, the protection of 17β-estradiol was associated with GSK-3β.